Hubungan Jenis Kelamin, Status Gizi, dan Berat Badan Lahir Rendah dengan Kejadian Kejang Demam pada Anak di RSUD Abdoel Wahab Sjahranie Samarinda: The Relationship Between Gender, Nutritional Status, and Low Birth Weight with The Incidence of Febrile Seizures in Children at the RSUD Abdoel Wahab Sjahranie Samarinda - Muhammad Harbiyan Acikdin; Annisa Muhyi; Vera Madonna Lumban Toruan (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2023)
The incidence of febrile seizures is the most common cause in the neuro field of children at the age of 6 months to 60 months, the incidence ranges from 2 to 5% of cases. Risk factors for febrile seizures such as gender, nutritional status, and low birth weight. This study aims to determine the relationship between gender, nutritional status, and low birth weight with the incidence of febrile seizures in children at the Abdoel Wahab Sjahranie Hospital, Samarinda. The study was carried out using observational analysis using a cross-sectional design. The research data were obtained from medical records at Abdoel Wahab Sjahranie Hospital Samarinda with a purposive sampling method. The sample of this study was children aged 6 months to 60 months who suffered from febrile seizures and fever without seizures and met the researcher's criteria. Statistical analysis using chi-square test. The results found as many as 184 samples of 92 samples of febrile seizures and fever without seizures each. The incidence of febrile seizures occurred in the group of children aged 13-24 months (42.4%) with a prevalence of 68.5% boys and 31.5% girls. Researchers used chi-square and obtained p-values for gender (p = 0.034), nutritional status (p = 0.715) and low birth weight (p = 0.412). The conclusion is that there is a relationship between gender and there is no relationship between nutritional status and low birth weight with the incidence of febrile seizures. Keywords: Gender, Nutritional Status, Low Birth Weight, Febrile Seizure Abstrak Kejadian kejang demam kasus tersering di bidang neuro anak di umur 6 bulan hingga 60 bulan, insiden berkisar 2 hingga 5% kasus kejadian. Faktor risiko kejang demam seperti jenis kelamin, status gizi dan Berat Badan Lahir Rendah (BBLR). Penelitian ini bertujuan mengetahui hubungan jenis kelamin, status gizi dan BBLR dengan kejadian kejang demam anak di RSUD Abdoel Wahab Sjahranie Samarinda. Penelitian dilaksanakan dengan analitik observasional menggunakan desain potong lintang. Data penelitian diperoleh dari rekam medik di RSUD Abdoel Wahab Sjahranie Samarinda dengan metode purposive sampling. Sampel dari penelitian ini adalah anak yang berumur 6 bulan hingga 60 bulan yang menderita febrile seizure dan fever without seizure serta memenuhi kriteria dari peneliti. Analisis statistik memakai uji chi-square. Hasil ditemukan sebanyak 184 sampel yang terdiri dari masing-masing 92 sampel kejang demam dan demam tanpa kejang. Kejadian febrile seizure terjadi pada kelompok anak berusia 13-24 bulan (42.4%) dengan prevalensi anak laki-laki 68.5% dan perempuan 31.5%. Peneliti memakai chi-square dan didapatkan p-value jenis kelamin (p = 0.034), status gizi (p = 0.715) dan BBLR (p = 0.412). Kesimpulan didapatkan bahwa terdapat hubungan antara jenis kelamin dan tidak terdapat hubungan antara status gizi dan BBLR dengan kejadian kejang demam. Kata Kunci: Jenis Kelamin, Status Gizi, BBLR, Kejang Demam